Manufacturing of Bathroom Wall Tile Composites from Recycled Low-Density Polyethylene Reinforced with Pineapple Leaf Fiber - Negasi Gebremedhin; Gideon K. Rotich (International Journal of Polymer Science)
Plastic has been a dominant material for packaging in recent years but due to its nonbiodegradability, it is causing environmental pollution. Among the plastics used, low-density polyethylene is used abundantly. These plastics can be removed from the environment by recycling into useful products through reinforcing it with natural textile fibers into composite materials. Natural fiber-based composites are ecofriendly and low cost. This research is aimed at manufacturing composite wall tiles from recycled low-density polyethylene reinforced with pineapple leaf fibers (PALF). The PALF was extracted by the retting process followed by mechanical scratching and treated with 5% NaOH to improve the fiber-matrix interaction. The composites were manufactured by the melt-mixing method followed by compression molding. The effects of fiber length and fiber weight proportion on composite properties were investigated using tensile, flexural, impact, and water absorption tests. The study showed that the optimum fiber weight proportion and fiber length for the optimal properties of the composite were achieved at 30% fiber weight proportion and 30 mm fiber length. The maximum tensile strength of 1562 N/mm2, flexural strength of 454.9 N/mm2, and impact strength of 225.2 J/mm2 were obtained. Water absorption of the tiles increased with the increase in both the fiber weight proportion and the fiber length.